Correlation between sex and efficacy of immune checkpoint inhibitors (PD‐1 and CTLA‐4 inhibitors). Issue 1 (8th March 2018) - Wu, Yingcheng; Ju, Qianqian; Jia, Keren; Yu, Jingyan; Shi, Hui; Wu, Huiqun; Jiang, Maorong
Abstract : Immune checkpoint inhibitors (ICIs) exert the antitumor efficacy depending on immune response, which is affected by sex difference, where both biological and sociological factors are involved. The role of sex in ICI trials has been overlooked. How sex correlates with ICI efficacy is incompletely understood. Clinical trials evaluating ICI versus other therapies in male and female patients were included. The hazard ratio (HR) and 95% confidence interval (CI) of overall survival (OS) and progression‐free survival (PFS) were used. Six thousand and ninety‐six patients from 11 trials were included. More improvement of OS was observed in males (HR, 0.62; 95% CI, 0.53–0.71; p  < 0.001) treated with ICI versus controls than females (HR, 0.74; 95% CI, 0.65–0.84; p  < 0.001). ICIs improved PFS more in males (HR, 0.57; 95% CI, 0.43–0.71; p  < 0.001) than females (HR, 0.71; 95% CI, 0.52–0.91; p  < 0.001). The sex difference had more effect on the overall survival in melanoma patients versus NSCLC patients. Overall survival of patients treated with CTLA‐4 inhibitor was more influenced by sex variable compared with PD‐1 inhibitors. A significant sex‐related efficacy difference was observed between female and male melanoma patients. Although male patients had longer OS and PFS than females when treated with ICIs versus controls, the difference was not significant. Sex difference should be more considered in future clinical trials, guidelines and clinical practice. Abstract : What's new? A patient's gender is rarely considered during cancer therapy. However, it is possible that the effectiveness of therapies involving the immune system may differ between males versus females, as many immune functions differ according to sex. In this meta‐analysis, the authors analyzed the efficacy of immune‐checkpoint inhibitors in melanoma patients. They found that there do indeed appear to be significant sex‐related differences in the efficacy of these drugs. These results suggest that sex differences should be given greater weight in future clinical trials, guidelines and clinical practice.